Damit wir auch morgen noch gut leben können: A didactic and methodological convergence of ethic learning concerning religion education of the primary school by taking the example of responsibiliy for creation (Pedagogical Horizons, 2020)
This article deals with the question how to succeed with didactic and methodological approaches to sensitize pupils of primary schools to responsibility for creation and to kindle their awareness that every human being can make a contribution for a better place on earth even for our descendants.The topic focuses in particular on the priestly story of creation Gen 1,1-2,4a, specifically on the refrain “And God saw that it was good“.Based on the theological content of this biblical word and on the worth of meaningful narrations its meaning of acting in responsibility for creation will be shown by five issues (relationship, mindfulness, gratitude, ethic power of judgement and willingness).The didactical implementation in religion education is shown due to the five aspects mentioned and concretized by practical examples.
Keywords: Responsibility für creation, biblical story of creation, didactical implementation, religion education, primary school, ethic learning